Diagnóstico del posicionamiento competitivo de las microempresas de dulcerías artesanales de la zona norte de Manabí. - Cobeña Loor, José H. (2018)
The intention of this research project was to know the competitive positioning of the micro-companies dedicated to the artisanal production of sweets, of the note zone of Manabí and in turn these can contribute to the development of the Manabi market. In order to achieve this research, the market was studied through interviews and surveys as primordial techniques that were preceded by tools such as the interview guide and questionnaire, applied both to the owner and the economically active population of the different cantons of the northern area of Manabí, among them are Cantón Pedernales, Jama, Flavio Alfaro, El Carmen, San Vicente, Sucre, Chone, Pichincha, Rocafuerte, Tosagua, Bolívar and Junín. In order to know the competitiveness and the marketing of the main sweets manufacturing companies, several techniques were implemented such as the SWOT analysis that allowed to know a general perspective of the situation, the PEST analysis was used to understand the growth or decline of the market, the technique of the Competitive Profile Matrix (MPC) established the main competitive advantages among microenterprises. By knowing, understanding and applying these techniques, we proceeded to tabulate the data obtained in the surveys for their analysis and interpretation of the results achieved. Next, the design of an action plan was proposed, suggesting alternative solutions for the different areas of improvement of the microenterprises so that they contribute to the improvement of the positioning in the market. The final procedure according to the investigation required the drafting of conclusions and recommendations.